Work productivity among treatment‐naïve patients with genotype 1 chronic hepatitis C infection receiving telaprevir combination treatment. Issue 1 (16th February 2014) - Aggarwal, J.; Vera‐Llonch, M.; Donepudi, M.; Suthoff, E.; Younossi, Z.; Goss, T. F.
Summary: Work productivity is impacted in hepatitis C virus (HCV)‐infected patients and has been linked to treatment. In two Phase 3 trials, ADVANCE and ILLUMINATE, treatment‐naïve genotype 1 chronic HCV‐infected patients received 12‐week telaprevir (T) with 24 (T12PR24)‐ or 48 (T12PR48)‐week peginterferon alfa‐2a/ribavirin. The objective of this analysis was to examine the impact of chronic HCV infection and its treatment with combination therapy on work productivity. The 5‐item, self‐reported work productivity questionnaire (WPQ) was administered in Phase 3 trials to assess unemployment status, days unable to work due to HCV/treatment, reduced hours worked and impact on productivity in prior 4 weeks. Descriptive statistics and multivariate regression analyses were employed in analyses of pooled trial data. About 1147 patients were included; 22% ( n = 255) were unemployed at baseline, with 8% being unemployed due to health reasons. At week 12, there were no differences by treatment regimen in the number of days unable to work. At week 48, improvements were observed earlier among patients receiving the shorter duration of T combination treatment. Mean (95% CI) change from baseline in days unable to work was −0.48 (−0.85, −0.11) days for T12PR24, 1.43 (0.63, 2.24) days for T12PR48 and 1.24 (0.18, 2.30) days for PR48 with placebo. Predictors of days unable to work were identified and include demographic characteristics, pretreatment and on‐treatment levels of fatigue, as well regional variation. In post hoc analyses of the ADVANCE and ILLUMINATE trials, work productivity decreased during the initial 12 weeks regardless of treatment group.